Analysis of the career trajectory of women in leadership positions in the central region of Rio Grande do Sul - Milanesi, Camila Roriz (2024)
The participation of women in the labor market did not happen suddenly. For this, women began to work intensely and strategically on their career and leadership trajectory (Chagas et al., 2022; Dantas, 2023). This study aims to carry out an analysis of the career trajectory of women in leadership positions in the central region of Rio Grande do Sul and in different areas of activity, namely commerce, civil construction, politics, agribusiness and the Brazilian army. For this, a descriptive and qualitative research was carried out, based on semi-structured interviews with a sample of five women in leadership positions. After content analysis, it was possible to perceive from the findings that the formation, the support of the family and the companies in which the interviewees worked were fundamental for their development. In addition, they faced prejudices during their trajectories, but that made them grow, making this double life pleasant and harmonious, motivating them more and more.